Relationships among physical activity, regulatory emotional self-efficacy, psychological detachment, and job burnout among urban workers - Xu, Ke; Jiang, Hongyu; Wang, Huilin (Frontiers in Public Health, 2025)
IntroductionUrban workers face a series of negative stimuli in the contemporary workplace, such as faster work pace, disproportionate income to effort, and job insecurity. These negative stimuli are often among the causes of job burnout in urban workers. Burnout among workers can negatively affect their families, businesses, and their own physical and mental well-being. Therefore, the emergence of burnout symptoms among urban workers has become a pressing issue. Addressing how to alleviate job burnout and improve their physical and mental well-being is the focus of this study.MethodsThis cross-sectional study employed snowball and convenience sampling methods, collecting 395 valid responses from urban young and middle-aged workers across the public service, manufacturing, service, and information technology industries in Hunan, Jiangxi, and Anhui provinces, China. Structural equation modeling was performed using SmartPLS 4 to examine the proposed hypotheses.ResultsThe results indicated that physical activity was positively associated with regulatory emotional self-efficacy and psychological detachment (β = 0.446, p < 0.001; β = 0.343, p < 0.001, respectively). Furthermore, regulatory emotional self-efficacy was also positively related to psychological detachment (β = 0.494, p < 0.001). Both variables showed significant negative associations with job burnout (β = −0.307, p < 0.001; β = −0.400, p < 0.001, respectively). In addition, regulatory emotional self-efficacy and psychological detachment had a significant negative mediating effect on the relationship between physical activity and job burnout (standard indirect effect = −0.362, p < 0.001).DiscussionThis implies that urban young and middle-aged workers who engage in physical activity are more likely to develop stronger regulatory emotional self-efficacy and psychological detachment, which in turn helps reduce job burnout. To better mitigate job burnout in urban young and middle-aged workers, governments, businesses, and individuals should emphasize the importance of physical activities.